Factors Influencing Smoking Behavior among University Students - Purba, Khairunnisa Insani; Febrianti, Afni; Nadhiroh, Al Kafi Mumtazah; Putri, Dinda Aulia; Ultami, Juwita Nisa; Nafisah, Tirara Yunami (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2025)
This study aims to identify factors influencing smoking behavior among university students, focusing on the influence of attitudes toward the lack of sanctions and attitudes toward cigarette sales. A quantitative methodology was used to measure the relationship between these variables. The study was conducted over a one-month period, involving 100 randomly selected university students as respondents. Primary data was collected through a questionnaire designed to explore students' attitudes, social norms, and behaviors toward smoking. An ethnographic approach and a normative paradigm were applied to understand the social and cultural contexts that influence student behavior. Secondary data in the form of journals, books, and scientific articles were used to support the analysis. Data collection techniques included questionnaires, observation, and documentation to capture broader aspects of smoking behavior. Data validity was ensured through source triangulation, which integrated the results from questionnaires, observations, and supporting literature. Statistical analysis showed that attitudes toward the lack of sanctions had a significant positive influence on smoking behavior, while attitudes toward cigarette sales were insignificant. The coefficient of determination (R²) of 93.6% indicates that the regression model has very high predictive power, although multicollinearity was found among the independent variables. The results of this study reveal that social influence and sanction regulations play a significant role in driving college students' smoking behavior. This study highlights the importance of stricter sanction enforcement policies and a social norms-based approach to reducing smoking prevalence. Further research is needed to explore other factors, including cultural and psychosocial aspects, to provide a more comprehensive understanding of the dynamics of smoking behavior among college students.